2019
DOI: 10.1038/s41436-019-0493-2
|View full text |Cite|
|
Sign up to set email alerts
|

Variant classification changes over time in BRCA1 and BRCA2

Abstract: Purpose: To report BRCA1 and BRCA2 (BRCA1/2) variant reassessments and reclassifications between 2012 and 2017 at the Advanced Molecular Diagnostics Laboratory (AMDL) in Toronto, Canada, which provides BRCA1/2 testing for patients in Ontario, and to compare AMDL variant classifications with submissions in ClinVar. Methods: Variants were assessed using a standardized variant assessment tool based on the American College of Medical Genetics and Genomics/Association for Molecular Pathology's guidelines and tracke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 35 publications
(61 reference statements)
3
35
1
Order By: Relevance
“…The rate at which specific VUS were reclassified as pathogenic or likely pathogenic variants was 5.6% (6/108) and that specific VUS reclassified as benign or likely benign variants was 27.8% (30/108). These rates were comparable to those observed in previous studies ( Table 4 ) [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The rate at which specific VUS were reclassified as pathogenic or likely pathogenic variants was 5.6% (6/108) and that specific VUS reclassified as benign or likely benign variants was 27.8% (30/108). These rates were comparable to those observed in previous studies ( Table 4 ) [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have shown that about 10%–15% of the cases tested for BRCA exhibited a pathogenic variant [ 20 ]. Further, previous studies have reported a range of prevalence for BRCA VUS (3.9%–22.5%) [ 7 8 9 10 11 21 22 ]. However, these results are primarily from breast cancer studies, as there are very few studies that have solely focused on gynecological oncology.…”
Section: Discussionmentioning
confidence: 99%
“…One example of this is the reclassification for BRCA1 and BRCA2 variants over time, most often downgrading. 24,25 Traditionally the classification of (pathogenic) variants was based on the ascertainment from the more severe Mendelian disorders. Now, with more data available from population studies, reduced penetrance of variants is becoming clearer as is demonstrated by these kind of variants found in individuals without a Mendelian phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Any discrepancy should be reviewed by both the molecular pathologist and clinician, and prior reports should be reviewed. Importantly, recent data suggest that many VUS will eventually be classified as benign (82)(83)(84)(85)(86) and can usually be resolved with subsequent clinical correlations, in discussions between the molecular diagnostician, clinician, and the patient.…”
Section: Genetic Data Analysismentioning
confidence: 99%